Pembentukan Karakter Melalui Pembelajaran Amsilati Di SMP Salafiyah Pekalongan - Dewi Anggraeni; Ningrum Ningsih; Kholisna Afiati (Al-Riwayah : Jurnal Kependidikan, 2023)
Character education is fundamentally integrated into the learning process, one of which is Amsilati learning, a unique education program held at Pekalongan Salafiyah Middle School. This study aims to reveal the formation of student character in learning. This study used a qualitative descriptive method with data sources from the academic community of SMP Salafiyah Pekalongan. Data collection techniques through interviews, observation, and documentation studies were then analyzed using qualitative data analysis techniques. The results of this study show: a) Amsilati's learning process is very closely related to the formation of student character based on an active learning design with a student-active learning approach; b) There are ten character values ​​contained in Amsilati learning; c) Character building emphasizes three main aspects in the form of knowledge, habituation, and moral wisdom.